Organoleptic Characteristics of Rimau Gerga Lebong (RGL) Orange Coated With Cassava Peel Starch and Chitosan Saved at Temperature Room For 20 Days - Adwini Prasetya; Siska Apriani; Sigit Mujiharjo (Badan Penerbitan Fakultas Pertanian (BPFP), 2020)
Consumers’ preference level, especially on agricultural or food products, can be used as a benchmark measure or determine the market or shelf life of the product. This research aims to determine organoleptic quality through the level of people's preference for RGL citrus fruits coated with edible coating starch from cassava peel plus chitosan. Aplication of coating on the fruits and storage layout of this study was conducted following a completely randomized design (CRD) with 2 different factors; cassava skin starch concentration; namely 3%, 5%, and 7%; and chitosan concentration; i.e. 0%, 0.5%, 1%, 1.5%. The observed variables are the panelists’ preference level with organoleptic test on color, flavor, texture and taste of RGL orange that has been treated and stored at room temperature for 20 days. Research result indicates that the color of the orange that the panelists favored is absent; the level of panelist most prefer is neutral, if the starch is 3% with chitosan 0% (preference score 3.92); and if the starch 7% with chitosan 0.5% (score 3.44). The preferred aroma of orange is absent; the level of panelist highest preference on aroma is neutral, if the starch is 5% with chitosan 1.5% (score 3.12); and if the starch 7% with chitosan 0.5% (score 3.04). The texture of the orange is preferred to be absent; the level of panelist higherst preference on texture is neutral, if the starch is 7% with chitosan 0.5% (score 3.60); and if the starch is 3% with chitosan 0.5% (score 3.56). The taste of citrus fruits is preferred if the starch is 7% with chitosan 0.5% (score 4.00); and if the starch is 3% with chitosan 0% (score 3.44). Therefore, RGL citrus fruits can be stored at room temperature for up to 20 days, if it is coated with 7% cassava peel starch with 0.5% chitosan